Identification of a novel gut microbiota signature associated with colorectal cancer in Thai population - Iadsee, Nutta; Chuaypen, Natthaya; Techawiwattanaboon, Teerasit; Jinato, Thananya; Patcharatrakul, Tanisa; Malakorn, Songphol; Petchlorlian, Aisawan; Praditpornsilpa, Kearkiat; Patarakul, Kanitha (Scientific reports, 2023)
Colorectal cancer (CRC) is the third most common cancer worldwide. Dysbiosis of human gut microbiota has been linked to sporadic CRC. This study aimed to compare the gut microbiota profiles of 80 Thai volunteers over 50 years of age among 25 CRC patients, 33 patients with adenomatous polyp, and 22 healthy controls. The 16S rRNA sequencing was utilized to characterize the gut microbiome in both mucosal tissue and stool samples. The results revealed that the luminal microbiota incompletely represented the intestinal bacteria at the mucus layer. The mucosal microbiota in beta diversity differed significantly among the three groups. The stepwise increase of Bacteroides and Parabacteroides according to the adenomas–carcinomas sequence was found. Moreover, linear discriminant analysis effect size showed a higher level of Erysipelatoclostridium ramosum (ER), an opportunistic pathogen in the immunocompromised host, in both sample types of CRC patients. These findings indicated that the imbalance of intestinal microorganisms might involve in CRC tumorigenesis. Additionally, absolute quantitation of bacterial burden by quantitative real–time PCR (qPCR) confirmed the increasing ER levels in both sample types of cancer cases. Using ER as a stool–based biomarker for CRC detection by qPCR could predict CRC in stool samples with a specificity of 72.7% and a sensitivity of 64.7%. These results suggested ER might be a potential noninvasive marker for CRC screening development. However, a larger sample size is required to validate this candidate biomarker in diagnosing CRC.